Bulgaria : 2012 Article IV Consultation--Staff Report; Public Information; and Statement by the Executive Director for Bulgaria. (IMF Staff Country Reports; Country Report, 2012)
Bulgaria did not have any exchange rate crisis, international bailout, bank intervention, or build-up of public debt. This attests to the strength of the policy framework and policy implementation. The fiscal adjustment achieved so far should be preserved, but improving the composition of the budget would support growth. The financial system is stable with high buffers, but the low growth environment poses challenges. Executive Directors suggest the need for some structural reforms.